"What is Feminism?" Perceptions of brazilian adults (Research, Society and Development, 2022)
The objective of this study was to investigate what adults know about feminism in Brazil by replying to this question: “What is feminism for you?”. Participants were 731 Brazilian adults between 18 and 79 years old (M = 30.83; SD = 11), mostly women (78%), single (59%), and born in the state of Rio Grande do Sul/Brazil (77%). Descriptive statistics were performed in the Statistical Package for the Social Sciences (SPSS) version 22.0 and the responses to the question analyzed in IRAMUTEQ (Interface de R pour analyses Multidimensionelles de Textes et de Questionnaires) version 0.7. The result was a dendrogram formed by two axes, two subaxes and four classes. The axis “Conflicting stereotypes and perceptions” was formed by the class “Divergent understandings” and the axis “Social movement” was formed by the sub-axes “Objectives and struggle” (containing two classes) and “Social advances” (containing one class). In general, the answers indicate proper understanding on feminist issues and its importance to a less unequal society, which contrasts with the anti-feminist discourse enhanced by the current conservative wave in Brazil.